Antimicrobial Therapeutics in Regenerative Endodontics: A Scoping Review - Ribeiro, Juliana S.; Miinchow, Eliseu A.; Bordini, Ester A. Ferreira [UNESP]; Oliveira da Rosa, Wellington Luiz de; Bottino, Marco C. (Elsevier B.V., 2020)
Introduction: This review aimed to provide a critical appraisal of alternative antimicrobial strategies in lieu of traditional triple antibiotic paste (TAP). Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The literature search was performed in 8 databases (PubMed/Medline, Embase, LILACS, Web of Science, Scopus, BVS, SciELO, and the Cochrane Library), selecting clinical, in vitro, in vivo, and in situ studies that evaluated antimicrobial alternatives to TAP in regenerative endodontics. Studies lacking an experimental TAP group were excluded. Results: A total of 1705 potentially relevant records were initially identified. From the 38 studies retrieved for full-text reading, 16 fulfilled all selection criteria and were included in the qualitative analysis. According to the study design, 11 studies were solely in vitro, 1 study was both in vitro and in vivo (animal model), 2 studies were solely animal experiments, and 2 studies were clinical trials. The alternative antimicrobial agents to TAP consisted of modified TAP formulations (eg, a combination of TAP with chitosan); TAP-eluting nanofibers; propolis; chlorhexidine (CHX) gels/solutions; double antibiotic pastes composed of distinct combinations of antibiotics; Ca(OH)2-based formulations; and sodium hypochlorite. Overall, most of the alternative agents performed similarly to TAP, although some strategies (eg, Ca(OH)2- and CHX-based formulations) seemed to present dubious importance in the control of infection. Conclusions: TAP still remains an excellent option in terms of the complete elimination of microorganisms. This review points to the use of electrospun fibers as a drug delivery system to offer a controlled release of the antimicrobial agent, as well as the use of natural compounds, deserving future investigation.
Keywords: Antimicrobial agents; natural compounds; regenerative endodontics; scoping review